Effect of L- Carnitine Supplementation During in vitro Maturation on Oocyte Maturation and Cleavage Rate in Sahiwal Cows - Singh, Khushpreet; Singh, Narinder; Kaur Mavi, Gurjot; Honparkhe, Mrigank; Shekhar, Apoorva; Singh, Prahlad (The Indian Journal of Animal Reproduction, 2025)
The experiment was conducted to study the effect of supplementation of L-Carnitine in maturation media on oocyte maturation. Cumulus oocyte complexes (COC’s) obtained by follicular aspiration having at least a complete layer of cumulus cells were randomly divided into two groups containing 10 replicates each of 10-12 oocytes. In vitro matura tion of the COC’s supplementation with 3 mM L-Carnitine showed (Mean± Std. Error; %) significantly lower (p<0.05) complete expansion of cumulus cells (8.00±0.36; 72.07) in comparison to control (10.10± 0.94; 89.38). On the other hand, COC’s showing intermediate expansion were significantly high (p<0.05) in maturation media (Mean±S.E.; %) supplemented with 3 mM L-Carnitine (2.00±0.21; 18.02) in comparison to control (0.50±0.22; 4.42) indicating that sig nificantly high number of COC’s were unable to attain complete cumulus expansion in maturation media supplemented with 3 mM L-Carnitine. The cleavage rate of the COC’s matured with supplementation of 3 mM L-Carnitine showed (Mean±S.E.; %) lower cleavage (7.90±0.41; 72.47) in comparison to control (9.00± 0.88; 81.82), although not significant. IVM media supplemented with 3 mM L-Carnitine does not provides a favourable environment for in vitro maturation of bovine oocytes obtained though ovum pick-up and there is need to find optimum concentration of L-Carnitine which may suit the oocytes of the Sahiwal cows.